Edukasi Memelihara Kesehatan Gigi dan Mulut Madrasah Ibtidaiyah Al-Hidayah Cirendeu - Mutiah Apritawati (STIPAS Tahasak Danum Pambelum Keuskupan Palangkaraya, 2023)
Community service is a form of lecture that is carried out through a community empowerment program. This activity is one form of Catur Dharma Muhammadiyah higher education. MI Al Hidayah is the location of the school where the writer carries out community service. The right way to brush their teeth is the most important thing to get children used to brushing their teeth from an early age. Based on the above, counseling about dental and oral health education requires several special health protocols. The purpose of this community service is to raise awareness of healthy living, build habits to apply how to brush your teeth properly in everyday life, and it can become a habit to always maintain healthy teeth and mouth. As a result of this activity, it is hoped that students can understand dental and oral health and apply it in everyday life. This activity was carried out to teach students how to brush their teeth properly, then students were given a set of dental kits to practice how to brush their teeth directly.